Tracing the Long-Term Evolution of Land Cover in an Alpine Valley 1820–2015 in the Light of Climate, Glacier and Land Use Changes - Hohensinner, Severin; Atzler, Ulrike; Fischer, Andrea; Schwaizer, Gabriele; Helfricht, Kay (Frontiers in Environmental Science, 2021)
Glacial Alpine environments and their fluvial systems are among those landscapes most comprehensively affected by climate change. Applying a ‘regressive-iterative GIS reconstruction method’ enables identifying land cover changes between 1820 and 2015 in the LTER site ‘Jamtal’ (Tyrol, Austria) based on historical maps and optical remote sensing data. Below 2,100 m a.s.l. the Jamtal experienced a massive 62 % decline of unvegetated debris and rock areas (so-called ‘wasteland’) that was mainly transformed to grassland and sparsely wooded areas. Forests increased by an outstanding 323 % and grassland was replaced by sparsely or densely wooded areas. This primarily reflects the abandonment of agricultural uses in unfavourable remote sites. In the higher (formerly) glaciated subbasin, glaciers declined by 55 %, which was associated with a major (82 %) growth of exposed wasteland. Concurrently, Alpine grassland expanded by 196 % and krumholz even by 304 %. Approximately half of the new fluvial system that evolved in deglaciated areas between 1870 and 1921 still existed in 2015. Unconsolidated debris buried almost one fifth of the new channels, and almost one third was colonized by vegetation. Recent data show that the deglaciation process is much faster than the colonization process by Alpine vegetation. Accordingly, the extent of wasteland has expanded and potentially amplifies the sediment supply of the fluvial system. The long-term investigation of the Alpine landscape reveals that the transformation processes have accelerated in recent decades.